Perturbed hematopoietic stem and progenitor cell hierarchy in myelodysplastic syndromes patients with monosomy 7 as the sole cytogenetic abnormality. - Dimitriou, M; Woll, P; Mortera-Blanco, T; Karimi, M; Wedge, D; Doolittle, H; Douagi, I; Papaemmanuil, E; Jacobsen, S; Hellström-Lindberg, E (Impact Journals, 2016)
The stem and progenitor cell compartments in low and intermediate-risk myelodysplastic syndromes (MDS) have recently been described, and shown to be highly conserved when compared to those in acute myeloid leukemia (AML). Much less is known about the characteristics of the hematopoietic hierarchy of subgroups of MDS with a high risk of transforming to AML. Immunophenotypic analysis of immature stem and progenitor cell compartments from patients with an isolated loss of the entire chromosome 7 (isolated -7), an independent high-risk genetic event in MDS, showed expansion and dominance of the malignant -7 clone in the granulocyte and macrophage progenitors (GMP), and other CD45RA+ progenitor compartments, and a significant reduction of the LIN-CD34+CD38low/-CD90+CD45RA- hematopoietic stem cell (HSC) compartment, highly reminiscent of what is typically seen in AML, and distinct from low-risk MDS. Established functional in vitro and in vivo stem cell assays showed a poor readout for -7 MDS patients irrespective of marrow blast counts. Moreover, while the -7 clone dominated at all stages of GM differentiation, the -7 clone had a competitive disadvantage in erythroid differentiation. In azacitidine-treated -7 MDS patients with a clinical response, the decreased clonal involvement in mononuclear bone marrow cells was not accompanied by a parallel reduced clonal involvement in the dominant CD45RA+ progenitor populations, suggesting a selective azacitidine-resistance of these distinct -7 progenitor compartments. Our data demonstrate, in a subgroup of high risk MDS with monosomy 7, that the perturbed stem and progenitor cell compartments resemble more that of AML than low-risk MDS.